Preparation of Bilayer YBa2Cu3O7-x -NayCoO2 Thermoelectric Ceramic by Solid-state Sintering Method - Pimpilai Wannasut (Science Faculty of Chiang Mai University, 2019)
Segmented thermoelectric materials have recently been of interest for many heat regulation-related applications such as those in automotive and electronics industries. They are found be highly efficient in converting heat-to-electricity and vice versa. This work attempts to investigate the preparation of bilayer thermoelectric YBa2Cu3O7-x-NayCoO2 or YBCO-NCO ceramics. YBCO and NCO powder were calcined at 850°C for 12 h and 750°C for 16 h, respectively. The bilayer was successfully fabricated by conventional sintering method at 900°C for 18 h under a normal atmosphere. YBCO showed pure phase with orthorhombic structure and NCO showed pure phase with hexagonal structure. Cylindrical shaped YBCO-NCO samples sintered under this condition showed complete bilayer and good bonding at the interface.